Serum Vitamin D and Anti-Müllerian Hormone Levels in Patients with Ovarian Dysfunction: A Cross-Sectional Analysis or metaanalysis - Neena Jamil, Nishat Akram, Heebah Shabbir, Wajiha Mehwish, Saima Abid, Muhammad Ahmer Shoaib (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Objective: To investigate the association between serum 25-hydroxyvitamin D [25(OH)D] and Anti-Müllerian Hormone (AMH) in women with ovarian dysfunction.